Development of MAILI 21 (Lectora inspire 21 interactive learning media) to improve student learning outcomes in elementary schools - Novina Fitri Astuti; Susilo Tri Widodo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Learning Pancasila and Citizenship Education which is less varied and innovative causes students to be less enthusiastic and bored quickly. Therefore, it is necessary to combine learning with IT-based media with conventional media to improve student learning outcomes. This study aims to develop interactive learning media Lectora Inspire and determine the feasibility, practicality, effectiveness, and able to improve student learning outcomes in the subject of Pancasila and Citizenship Education material united in diversity in grade III SD. This research uses the Borg and Gall model which is limited to stage eight. Starting with data collection, planning, product design, expert validation of products, product revision, product trials, product usage trials and final product revision. The research subjects consisted of 1 material expert, 1 media expert, 1 class teacher, 9 students for small-scale trials, and 13 students for large-scale trials. Data collection techniques used interviews, validation sheets, response questionnaires, and tests. The material expert validation results reached 90% with the "very feasible" category, the media result validation value reached 85% with the "feasible" category, and the media practicality value reached 90% with the "very practical" category.  The media was also declared effective which can be seen from the pretest and posttest results with an average difference of 19 and the T-test results. Thus, the development of Lectora Inspire interactive media is concluded to be very feasible, practical, and effective in improving student learning outcomes.